다공성 구형 탄소를 이용한 리튬/유황 전지의 수명개선 및 전기화학특성 연구 - 허성규; 임수아; Hur, Sung Kyu; Lim, Soo A (전기화학회지, 2021)
Dissociation into Lithium-polysulfide electrolyte due to repeated cycles during the Lithium/Sulfur battery reaction is a major problem of reduced battery lifespan. We searched for a porous carbon with a large specific surface area that infiltrated S to prevent liquid Lithium-polysulfide from being dissolved in electrolyte, induce adsorption of Lithium-polysulfide, and further increase conductivity. In order to obtain porous carbon spheres with a large specific surface area, the carbon spheres of 1939 m2/g were raised to 2200 m2/g through additional KOH treatment. In addition, through heat treatment with S, a carbon sulfur compound containing 75 wt% of S was fabricate and material analysis was conducted on the possibility of using the cathode material. The electrochemical characteristics of the Reference (622; sulfur: 60%, conductive material: 20%, binder: 20%) pouch cell and the pouch cell made using 75wt% of carbon sulfur compound were analyzed. 75wt% of carbon sulfur pouch cell showed a 20% increase in lifespan and 10% improvement in C-rate compared to the Reference pouch cell after 50 cycles. 리튬/유황 전지 반응에서 리튬-폴리설파이드(Lithium polysulfide)는 사이클이 반복될수록 전해액에 해리되어 전지 수명을 저하시키는 큰 원인으로 작용한다. 액체 상태인 리튬-폴리설파이드가 전해액에 용해되지 않도록 유황을 담지하고 리튬-폴리설파이드의 흡착을 유도, 추가로 전도도까지 높일 수 있는 비표면적이 큰 다공성 탄소를 모색했다. 본 논문에서는 비표면적이 큰 다공성 탄소 구체를 얻기 위해 추가로 KOH 처리를 통해 1939 m2/g의 탄소 구체를 2200 m2/g으로 높였다. 또한, 유황과의 열처리를 통해 75wt%의 유황이 함유된 탄소 유황 화합물을 만들어 양극재료 사용가능성에 대한 물질 분석을 진행했다. Reference (622; 유황: 60%, 도전재: 20%, 바인더: 20%) 파우치 셀과 75 wt%의 탄소 유황 화합물을 이용하여 만든 파우치 셀의 전기화학적 특성 분석을 진행하였다. 이는 50 사이클 기준으로 Reference 대비 20%의 수명 증가와 10%의율 특성 향상을 보였다.